199k views
11 votes
Use the vertex of the function (h, k) and the x-intercepts . g(x) = 2 * (x + 3) ^ 2 - 6

Use the vertex of the function (h, k) and the x-intercepts . g(x) = 2 * (x + 3) ^ 2 - 6-example-1
User Foufa
by
4.0k points

1 Answer

7 votes

Answer:

Hope this helps

Explanation:

Use the vertex of the function (h, k) and the x-intercepts . g(x) = 2 * (x + 3) ^ 2 - 6-example-1
Use the vertex of the function (h, k) and the x-intercepts . g(x) = 2 * (x + 3) ^ 2 - 6-example-2
Use the vertex of the function (h, k) and the x-intercepts . g(x) = 2 * (x + 3) ^ 2 - 6-example-3
User Mike Breen
by
4.8k points